A closer look at the Tillya-tepe folding crown and attached pendants. Issue 1 (April 2020) - Peterson, Sara
Abstract : Tillya-tepe, the 1 st century AD burial site, was situated in ancient Bactria, modern Afghanistan. Among the numerous gold artefacts found in the six excavated graves was a spectacular gold crown worn by a high status woman. This article analyses the design and iconography of this crown against the backdrop of a number of factors, including the steppe nomadic heritage of the Tillya-tepe people, and the presence of Graeco-Roman style imagery which appears on some of their most important possessions.